Green and Sustainable Payment Systems for Advancing U.S. Climate Goals - Prakash Raju Kantheti; Prof. Stella Bvuma (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
In every industry, including finance, new solutions are required due to the rapid rate of climate change. Sustainable and eco-friendly payment methods have become vital tools for tying economic activity to green objectives. The potential of sustainable financial infrastructures to reduce carbon footprints, incentivise environmentally conscious consumer behaviour, and ease the shift to a low-carbon economy is highlighted in this article’s investigation of their role in advancing US climate objectives. Green infrastructure’s ability to mitigate the anticipated rise in excessive precipitation or warmth is usually linked to its benefits for climate adaptation. Benefits include reducing the incidence of combined storm and sewer overflows (CSOs), improving storm-water runoff management, conserving water, preventing flooding, accommodating natural hazards (such as moving out of floodplains), lowering ambient temperatures and the effects of urban heat islands (UHIs), and protecting against sea level rise (with the possibility of storm-surge protection measures). Additionally, according to the U.S. Environmental Protection Agency (EPA), green infrastructure can improve air quality and human health, reduce energy consumption, save capital costs, increase carbon storage, increase recreational space and wildlife habitat, and even raise land values by as much as 30%. Important developments include energy-efficient digital currencies, more effective blockchain technology, and carbon offset systems that emphasise accountability and transparency. These systems may operate as catalysts for environmental advancement by incorporating sustainability measures into financial transactions, increasing the efficiency of payment processing, and integrating renewable energy sources. In order to ensure that payment systems become a key component in attaining a sustainable future, the report ends with policy proposals to encourage adoption, including as regulatory frameworks, public-private collaborations, and consumer awareness campaigns.